Penguatan Sinergi Jaringan Sosial dan Program Kesehatan untuk Mengurangi Stunting di Desa Wates, Kecamatan Pagu, Kabupaten Kediri - Reta, Putri Seifera Marga; Ummah, Zuhrotul; Adawiyah, Dewi Mufidah; Zuhri, M. Agus Saifudin; Meizar, Danun Qoyyum; Handayani, Diah (Welfare : Jurnal Pengabdian Masyarakat, 2024)
The problem of stunting in Wates Village, Pagu District, Kediri Regency, is a serious concern because it has an impact on the quality of life and productivity of the community. One of the main factors influencing stunting prevention is weak synergy between social networks and health programs. This community service activity aims to strengthen collaboration between the community, health cadres and village government to increase the effectiveness of stunting prevention. The approach used is the Participatory Action Research (PAR) method, which involves identifying local assets, training cadres, and facilitating dialogue between stakeholders. This activity resulted in increased community awareness about the importance of nutrition and parenting, as well as the formation of a working group to support village health programs. The results show that strengthening social networks, combined with health program interventions, is able to create an effective synergy in reducing stunting rates. This program is expected to become a sustainable model for other villages.